The quality of sperm preparation medium affects the motility, viability, and DNA integrity of human spermatozoa - Fatemeh Anbari (Journal of Human Reproductive Sciences, 2016)
Aim: The goal was to compare the effects of three different sperm preparation media on sperm motility, viability, and DNA integrity of semen samples from normozoospermic men. Methods: A total of 15 normozoospermic males were included in the study. The semen analysis (SA) was performed in accordance with the WHO guidelines (2010). After SA, each sample was divided into three aliquots, and swim-up was performed with three different sperm preparation media (Sperm Preparation Media, Origio, Denmark; Ham′s F10, Biochrome, Berlin, Germany; and VitaSperm TM , Innovative Biotech, Iran). Sperm motility, viability, and DNA fragmentation were evaluated at 0, 1, 2, and 24 h after swim-up. Results: There were no significant differences, at any time intervals, in the total sperm motility between the different sperm preparation media. However, the rate of progressive motility was significantly higher in spermatozoa prepared using the media from Origio in comparison with VitaSperm TM (P = 0.03), whereas no significant difference was found against Ham′s F10 medium. No significant differences in sperm viability were seen between the media products. However, 1 h after swim-up, the extent of sperm DNA fragmentation was lower in the medium from Origio versus VitaSperm TM (P = 0.02). Conclusions: The data showed that the quality of medium for preparation of semen samples from normozoospermic men significantly affects the performance of spermatozoa in assisted conception programs.